Unmasking Social Science Imperialism : Globalization Theory As A Phase Of Academic Colonialism - Mentan, Tatah (Book collections on Project MUSE., 2015)
Contemporary social science is a product of the capitalist world-system and Eurocentrism is constitutive of the geoculture of this system characterized by the parochiality of its universalism, assumptions about the superiority of Western civilization and imposition as the sole theory of global progress. The creation of these structures of knowledge, specifically the institutionalization of the social sciences, is a phenomenon that is inextricably linked to the very formation and maturation of Europe's capitalist world system or imperialism. There is therefore nothing that is natural, logical, or accidental about the institutionalization of the social sciences. These Europeanized structures of knowledge are imposed ways of producing knowledge of the world. This Eurocentrism of social science has justifiably come under increasingly vigorous scrutiny, especially in the period since 1945 with the formal decolonization of Africa, Asia, and much of the Caribbean. This book forcefully argues that if social science is to make any progress in the twenty-first century, it must overcome its Eurocentric heritage that has distorted social analyses and its capacity to deal with the problems of the contemporary world and embrace other non-Western funds of knowledge production.